2021
DOI: 10.3390/ijms22094657
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nonshivering Thermogenesis Genes on Leptin Levels Regulation in Residents of the Coldest Region of Siberia

Abstract: Leptin plays an important role in thermoregulation and is possibly associated with the microevolutionary processes of human adaptation to a cold climate. In this study, based on the Yakut population (n = 281 individuals) living in the coldest region of Siberia (t°minimum −71.2 °C), we analyze the serum leptin levels and data of 14 single nucleotide polymorphisms (SNPs) of 10 genes (UCP1, UCP2, UCP3, FNDC5, PPARGC1A, CIDEA, PTGS2, TRPV1, LEPR, BDNF) that are possibly involved in nonshivering thermogenesis proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In a subsequent study in Korean women, Cha et al found an association between rs3811787 and rs1800592 and body fat accumulation and obesity [ 30 ]. Moreover, Nikaranova’s study [ 32 ] showed the influence of rs3811787 on the leptin-mediated thermoregulation mechanism. In this study, the prevalence gradient of the rs3811787T allele of UCP1 increased from the south to the north across Eurasia, along the shore of the Arctic Ocean.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a subsequent study in Korean women, Cha et al found an association between rs3811787 and rs1800592 and body fat accumulation and obesity [ 30 ]. Moreover, Nikaranova’s study [ 32 ] showed the influence of rs3811787 on the leptin-mediated thermoregulation mechanism. In this study, the prevalence gradient of the rs3811787T allele of UCP1 increased from the south to the north across Eurasia, along the shore of the Arctic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence gradient of the rs3811787T allele of UCP1 increased from the south to the north across Eurasia, along the shore of the Arctic Ocean. Thereby, the authors suggest the potential involvement of the UCP1 gene, in particular the rs3811787 T allele, in better activation of the UCP1 gene and higher activity of BAT [ 32 ]. Our very preliminary data also confirmed the decreased risk of T2DM individuals possessing the rs3811787 TT genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerase chain reaction was performed on a BioRad T100 Thermal Cycler (Bio-Rad Laboratories, Inc., Hercules, CA, USA). The data, including the PCR product size, primer sequence, annealing temperature, and restriction enzymes, are given in Supplementary Table S1 [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, two studies compared populations from higher and lower altitude regions of Tibet, reporting that living at higher altitude had no effect on HM macronutrient content, 16 but was related to higher HM adiponectin and lower leptin concentrations; however, this could be in part explained by the higher body mass index (BMI) of mothers from lower altitude, 17 or lower circulating leptin as an adaption to colder climate in mothers from higher altitudes 18 …”
Section: Geographical Factorsmentioning
confidence: 99%